Analisis biaya Pengangkutan Sampah Dengan Menggunakan Kendaraan Roda Tiga Di Kelurahan Kairagi Dua Kota Manado - Ever N Slat; Teddy Takaendengan; Franky R Tombokan (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
In a waste management system, several systems are formed, all of which are interconnected and cannot be separated. One of the problems in urban waste management is the transportation system. For the transportation system, many use three-wheeled vehicles with an average vehicle age of over 10 years with a capacity of approximately 2 m3. This research was conducted in Manado City, especially in Kairagi Dua Village and the method used to obtain the distance traveled, the number of rounds, the number of transport vehicles, the volume of waste transported is by direct observation. To calculate the cost of transporting waste, mathematical calculations are used. From the data obtained it is known that Kairagi Dua Village is one of the villages in the Mapanget sub-district. Has a tricycle fleet of 4 (four) units. Transport capacity is 2 m3. Each vehicle has a total of 4 round trips per day. From the results of the analysis that has been carried out, the following results are obtained: 1) the farthest distance is 5.6 Km2) fixed costs per year are operational costs, fuel, workers' wages 3) waste transportation costs are operational costs plus labor costs plus fuel costs divided with the volume of waste transported. From the results of the analysis, it can be concluded that the average cost of transporting waste in Kairagi Dua Village using three-wheeled vehicles is Rp. 58,340/ton of waste